Pengaruh Pembelajaran Saintifik Bermuatan Kearifan Lokal terhadap Prestasi Belajar Matematika - Sebastianus Fedi; Ferdinandus Ardian Ali; Silfanus Jelatu (UNIKA SANTU PAULUS RUTENG, 2020)
The purpose of this study was to determine whether or not there is an effect of a scientific learning approach with local wisdom on students' mathematics learning achievement. The population were students of class II SMPN I Ruteng-Cancar for the 2018/2019 academic year. The sample was determined by random class. There were 64 students who were divided into two treatment groups. A total of 32 students in the experimental class and 32 students in the control class. The difference in effect between experimental action (scientific learning with local wisdom) and control action (conventional learning) is seen in the average difference test between these two groups. Data analysis used statistical t test, in which the sample groups are mutually independent. Obtained, tcount = 3,21 and ttable = 1,67. Because t_count > t_table then Ho: µ1 ≤ µ2 is rejected, otherwise H1: µ1 > µ2 is accepted. The conclusion is that learning with a scientific approach containing local wisdom has a positive and significant effect on student achievement.